Finite element analysis of rectangular composite plates subjected to a uniformly distributed load - Ng, Luke Yong Ning (Nanyang Technological University, 2023)
This project aims to analyse the effect of coupling on the bending response of a rectangular composite plate subjected to a uniformly distributed load. The commercially available finite element software, ANSYS, is used to study the effect of the coupling of B16 and B26 in anti-symmetric laminated composite plate with various types of simple supports. The anti-symmetric layup is [+theta, -theta]n where n represents groups of anti-symmetric stack and n=1, 2, 4 and 5 are investigated. The scope of work includes the finite element modelling and analysis of a case study with known exact solution for validation of the finite element model. After which this finite element model are used to study the effect of coupling and the effect of the different types of simple supports on the bending of anti-symmetric laminated composite plates subjected to a uniformly distributed load. The results presented in this report for the case study demonstrate good correlation with the exact solution, thereby validating the finite element model. It is worth noting that only the simply supported 3 condition allowed for obtaining results through theoretical calculations. By comparing these theoretical values to the values obtained through ANSYS simulations, the percentage error between the two sets of values was found to be less than 6%. This level of agreement strongly supports the validity of all the results obtained through the FEA simulations. The results of this project revealed several important trends in the behaviour of composite materials. Specifically, it was observed that increasing the fiber orientation from 0 to 90 degrees resulted in decreased deflection. Similarly, increasing the number of ply layers from 2 to 10 also led to a decrease in deflection. Furthermore, the project demonstrated the significant impact of the coupling effect on composite behaviour.